A Womxn’s Dis-ease - Hugo-Hamman, Chloë (My University, 2020)
This project seeks to reframe mental illness as a dis-ease versus a disease within biomedical discourse. It speaks to the ways in which mental illness is; pathologised, racialised, classed and gendered specifically in relation to “womxn”
A research report submitted in partial fulfilment of the requirements for the degree MA in Fine Art, to the Faculty of Humanities, University of Witwatersrand, Johannesburg, 2020